Takotsubo cardiomyopathy triggered by SARS-CoV-2 infection in a critically ill patient. Issue 6 (14th June 2020) - Taza, Fadi; Zulty, Mary; Kanwal, Arjun; Grove, Daniel
Abstract : COVID-19 became a global pandemic in early 2020. While well known for its pulmonary manifestations, the virus also has a number of cardiac manifestations as well. Takotsubo syndrome has scarcely been reported in patients with COVID-19, but it is possible that the cytokine storm associated with the infection can trigger Takotsubo syndrome in patients with underlying risk factors for Takotsubo (emotional distress, physical distress, history of psychiatric disorders).